The Importance of the Human Factor in Innovative Development - Abdukahorovna, Kamilova Nargiza (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The development of the information economy has significantly changed the place and role of man in a new type of management. The skills and abilities of a person came to the fore in social production. Human capital is a necessary condition for maintaining the competitiveness of the state economy in world markets, as well as the most important characteristic of the activities of the legislative and executive authorities in the country. To assess the quality of human capital, the standard of living, the level of education and longevity of the population, the state of medical care and the production of GDP per capita are measured.